THE IMPLEMENTATION OF TRANSPOSITION TRANSLATION PROCEDURES IN ENGLISH-INDONESIAN TRANSLATION OF EPIC MOVIE SUBTITLE - Anggraeni, Putri; Mujiyanto, Januarius; Sofwan, Ahmad (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
The topic of this research is The Implementation of Transposition TranslationProcedures in English-Indonesian Translation of Epic Movie Subtitle. Movie or filmcan be considered as the most popular literary work yet brings out language aspectsinto broaden. As we know, a lot of popular movies are written in English which ledtranslator produce a qualified translation of the movie in order to make the movieeasier to understand by the audiences. There are many translation proceduresimplemented in a movie translation, one of them is transposition translationprocedure. The goals of this final project are to reveal how many types and how thetransposition translation procedure is implemented in translating the subtitle of Epicmovie. This study used qualitative approach in describing the results of the analysisof transposition translation procedure implemented. In gathering data, the writerused two steps, they are watching and transcription. In analyzing data, the writerused several steps, they are identifying, classifying, reducing, and reporting. Afteranalyzing the data, the results of this research were presented by using thequalitative-descriptive method. There are 108 out of 1551 parts of subtitlesimplemented four types of transposition translation procedure. The results of theanalysis are described as follows: transposition translation procedure involvingliterary translation is 63.9%, transposition translation procedure involving change ofwords’ position 27.7%, transposition translation procedure involving change of wordclass 4.6%, and transposition translation procedure involving adjustment andreplacement of words 4.6%. It can be seen that the most frequently implementedprocedure is transposition translation procedure involving literary translation. Thetranslator implemented all types of transposition translation procedure in order toproduce a good translation which high in naturalness and equivalency of meaningbetween SL and TL.